2013
DOI: 10.1108/jd-10-2012-0133
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the information-coping trajectory of young people with long term illness

Abstract: Purpose -The purpose of this paper is to explore the relationship between information and coping from the experiences of young people coping with long term illness. Design/methodology/approach -Situational analysis was used as a methodological approach. It has roots in the Chicago Symbolic Interactionism School. Cartographic approaches enabled the analysis, mapping the complexities emerging from the data. Findings -As the young people became more informed about their health conditions, and gained knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…). Patients who are experts on their own diagnosis have been shown to cope better (Anne Sen and Spring ), have better self‐rated health status, and be less dependent on hospital care (Lorig et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…). Patients who are experts on their own diagnosis have been shown to cope better (Anne Sen and Spring ), have better self‐rated health status, and be less dependent on hospital care (Lorig et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…If certain information practices may produce negative emotions and result in inconsistent behaviors, other practices such as sharing information with other people appear to regulate the emotional response to information about the crisis (Chivers et al, 2020;Tandoc & Lee, 2020). Second, aligning with studies on HIB in the context of illness, the corpus of works analyzed here make emotions dependent on, and produced by, the situation in all its dimensions more than the search process itself, and many authors stress the entangled nature of emotions during information practices (Chivers et al, 2020;Eriksson-Backa, 2020;Ke et al, 2021;Rak, 2020;Sen & Spring, 2013;Song et al, 2021;Wong et al, 2021). The fact that, in real situations, emotions coexist and combine makes it a bit more difficult to understand them in connection to HIB, which leads to a third important implication.…”
Section: Digging At the Border Of The Unconsciousmentioning
confidence: 82%
“…According to McKenzie and Willson (2019), social interaction and information exchanges help to redefine oneself and a personal situation during "transitions", including situations of substantial change in a person's life, such as development of disease. In the context of illness, diversified information sources, experiences, and communication channels enable individuals to build the capacity to cope, while individual coping strategies allow individuals to deal with health situations through different information practices (Sen & Spring, 2013;Theis et al, 2021). The search for normality after a traumatic event, such as the diagnosis of a chronic disease, appears to be an information-based process in several studies (Genuis & Bronstein, 2017;Patel, Blandford, Stephenson et al Steinerová, 2019).…”
Section: Everyday Adaptationmentioning
confidence: 99%
“…Other studies have also shown that access via the internet has become increasingly important in recent years [ 30 ]. Through online communities, individuals experienced in dealing with their rare disease can eventually contribute to sharing information and even advise other families and health professionals [ 31 ]. Experts in this study emphasized that highly motivated families seek psychosocial support through this route, as it requires a high level of engagement.…”
Section: Discussionmentioning
confidence: 99%